Encyclopedia of social movement media - Downing, John (John Derek Hall); Gale Group (Thousand Oaks, California SAGE Publications, Inc., 2011)
Includes essays on the varied experiences of social movement media throughout the world in the 20th and 21st centuries.
List of entries -- Reader's guide -- About the editor -- Contributors -- Introduction -- A -- B -- C -- D -- E -- F -- G -- H -- I -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Y -- Z -- Index.
Electronic reproduction.
Keywords: Alternative mass media -- History -- 20th century -- Encyclopedias; Alternative mass media -- History -- 21st century -- Encyclopedias; Mass media -- Social aspects -- History -- 20th century -- Encyclopedias; Mass media -- Social aspects -- History -- 21st century -- Encyclopedias; Mass media -- Political aspects -- History -- 20th century -- Encyclopedias; Mass media -- Political aspects -- History -- 21st century -- Encyclopedias; Social movements -- History -- 20th century -- Encyclopedias; Social movements -- History -- 21st century -- Encyclopedias; Electronic books